MASCP gator: an overview of the Arabidopsis proteomic aggregation portal - Mann, Gregory W.; Calley, Paul C.; Joshi, Hiren J.; Heazlewood, Joshua L. (Frontiers in Plant Science, 2013)
A key challenge in the area of bioinformatics in the coming decades is the ability to manage the wealth of information that is being generated from the variety of high throughput methodologies currently being undertaken in laboratories across the world. While these approaches have made available large volumes of data to the research community, less attention has been given to the problem of how to intuitively present the data to enable greater biological insights. Recently, an attempt was made to tackle this problem in the area of Arabidopsis proteomics. The model plant has been the target of countless proteomics surveys producing an exhaustive array of data and online repositories. The MASCP Gator is an aggregation portal for proteomic data currently being produced by the community and unites a large collection of specialized resources to a single portal (http://gator.masc-proteomics.org/). Here we describe the latest additions, upgrades and features to this resource further expanding its role into protein modifications and genome sequence variations.